Tissue‐derived extracellular vesicles in cancers and non‐cancer diseases: Present and future - Li, Su‐Ran; Man, Qi‐Wen; Gao, Xin; Lin, Hao; Wang, Jing; Su, Fu‐Chuan; Wang, Han‐Qi; Bu, Lin‐Lin; Liu, Bing; Chen, Gang (Journal of extracellular vesicles, 2021)
Extracellular vesicles (EVs) are lipid‐bilayer membrane structures secreted by most cell types. EVs act as messengers via the horizontal transfer of lipids, proteins, and nucleic acids, and influence various pathophysiological processes in both parent and recipient cells. Compared to EVs obtained from body fluids or cell culture supernatants, EVs isolated directly from tissues possess a number of advantages, including tissue specificity, accurate reflection of tissue microenvironment, etc., thus, attention should be paid to tissue‐derived EVs (Ti‐EVs). Ti‐EVs are present in the interstitium of tissues and play pivotal roles in intercellular communication. Moreover, Ti‐EVs provide an excellent snapshot of interactions among various cell types with a common histological background. Thus, Ti‐EVs may be used to gain insights into the development and progression of diseases. To date, extensive investigations have focused on the role of body fluid‐derived EVs or cell culture‐derived EVs; however, the number of studies on Ti‐EVs remains insufficient. Herein, we summarize the latest advances in Ti‐EVs for cancers and non‐cancer diseases. We propose the future application of Ti‐EVs in basic research and clinical practice. Workflows for Ti‐EV isolation and characterization between cancers and non‐cancer diseases are reviewed and compared. Moreover, we discuss current issues associated with Ti‐EVs and provide potential directions.